Percepções do uso das TICs na educação de jovens - Takano, Guilherme Rafael Soares (2018)
The study aims to identify young students between 15 and 29 years old and their teachers’ ICT for education use perceptions. A qualitative exploratory research was done to analyze the ICT use in the EDUCAFRO environment. As data collection procedures were used: Literature revision, online survey and focal groups. This way, it was possible deepen young student’s own perceptions of ICT for education use knowledge and collaborate to the teacher’s in the same view. A non-coordinated use of ICT resources for education including hardware and software in EDUCAFRO was identified from the data collection and analyses. Considering the specific environment, other aspects were noted in the research context: Students are in a status-co ICT use rupture and the teachers are not able or find very difficult to keep their ICT for education knowledge, up to date.